1993
DOI: 10.2186/jjps.37.800
|View full text |Cite
|
Sign up to set email alerts
|

A CAD/CAM System for Removable Dentures. Part 1. A System for Complete Denture Fabrication.

Abstract: Abstract:The purpose of our study was to develop a computer aided system for designing and fabricating removable dentures (CAD/CAM system). In our newly developed system, anatomical and morphological information of denture space including edentulous residual alveolar ridges and surrounding tissues were obtained from a maxillomandibular double impression mounted on a high speed 3-D laser scanning machine. Artificial teeth arrangements, outline of polished surface, and denture border location were determined at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 3 publications
0
94
0
8
Order By: Relevance
“…The manufacturing of complete removable dental prostheses (CRDPs) by the computer-aided designing and manufacturing (CAD/CAM) methods, first documented in the 1990s 1,2) , have substantially increased in the last decade 3) . This technology-driven manufacturing process owes its exponential growth to a few important factors such as, but not entirely restricted to, the changing attitudes and/or trends of the clinicians as well as the dental technicians, the potential reduction in clinical chairside time and dental laboratory costs, as well as the incorporation of pre-polymerized materials.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturing of complete removable dental prostheses (CRDPs) by the computer-aided designing and manufacturing (CAD/CAM) methods, first documented in the 1990s 1,2) , have substantially increased in the last decade 3) . This technology-driven manufacturing process owes its exponential growth to a few important factors such as, but not entirely restricted to, the changing attitudes and/or trends of the clinicians as well as the dental technicians, the potential reduction in clinical chairside time and dental laboratory costs, as well as the incorporation of pre-polymerized materials.…”
Section: Introductionmentioning
confidence: 99%
“…Maeda et al [12] reported the pioneering work to design and fabricate complete dentures using CAD/CAM. They developed a computer-aided system including a work station for determining artificial tooth arrangements, occlusion, the outline of polished surface, and denture border location using a knowledge data base.…”
Section: Discussionmentioning
confidence: 99%
“…The digital methods in complete denture fabrication are not entirely new, as literature mentions such an approach as early as in 1994. 84 If we remember that it took more than three decades for digital protocols in fixed restorations to become mainstream, and considering that removable prosthodontics accounts for a significantly smaller portion of the dental business, it is likely that we will wait at least another decade for digital denture fabrication to become mainstream. While the clinical steps remain essentially analogic, digital technologies in complete denture may address some of the disadvantages of conventional denture fabrication protocols, like increased number of treatment visits, and questionable adaptation of denture bases to the tissues due to polymerization shrinkage.…”
Section: Fabrication Of Complete Prostheses Using Digital Protocolsmentioning
confidence: 99%